2011
DOI: 10.1103/physrevb.83.180410
|View full text |Cite
|
Sign up to set email alerts
|

Nonuniform switching of the perpendicular magnetization in a spin-torque-driven magnetic nanopillar

Abstract: International audienceTime-resolved scanning transmission x-ray microscopy measurements were performed to study the current-induced magnetization switching mechanism in nanopillars exhibiting strong perpendicular magnetic anisotropy. This technique provides both short-time (70 ps) and high-spatial (25 nm) resolutions. Direct imaging of the magnetization demonstrates that, after an incubation time of ∼1.3 ns, a 100 × 300 nm 2 ellipsoidal device switches in ∼1 ns via a central domain nucleation and opposite prop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 51 publications
(36 citation statements)
references
References 18 publications
2
34
0
Order By: Relevance
“…Indeed it was shown that the formation of domains and domain walls could be observed [11-13, 92, 93] and that it was influencing the slow magnetization switching dynamics. It influences fast dynamics as well as [54,55,91,92].…”
Section: Experimental Results Vs the Uniaxial Modelmentioning
confidence: 99%
“…Indeed it was shown that the formation of domains and domain walls could be observed [11-13, 92, 93] and that it was influencing the slow magnetization switching dynamics. It influences fast dynamics as well as [54,55,91,92].…”
Section: Experimental Results Vs the Uniaxial Modelmentioning
confidence: 99%
“…After the discovery of STT, it was soon realized 4,5 that the cylindrical symmetry of the magnetic properties in Perpendicular Magnetic Anisotropy (PMA) systems and the resilience to thermal fluctuations that the anisotropy provides would make PMA systems ideal playgrounds to explore STT-induced dynamics. However MTJs with relevant properties became available only a decade after 6 and relied on ultrathin systems where strong interfacial effects can be present 7 ; besides, efficient spin-torque generation requires complex embedding stacks 8,9 in which each additional layers can be a fluctuator strongly coupled to the layer of main interest in a non uniform 8,10 and non local 11 manner. As a consequence the STT-induced magnetization switching in PMA MTJ systems exhibits rich features 12,13 that deserve to be studied, especially as it opens opportunities in information technologies.…”
mentioning
confidence: 99%
“…In fitting our data to this model we obtain a dimensionless energy barrier of ξ = 450, which is within 25% of that expected based on the volume, magnetization and anisotropy of the nanomagnet (ξ = M s H k V /(2kT ) = 360). Our previous results, as well as those of many other groups, have found energy barriers to reversal for long field [20][21][22][23] and long current pulses (> 100 ns) 9,10 to be only a small fraction of that expected for a macrospin, suggesting the reversal proceeds by subvolume nucleation 24,25 . For similar samples, we found that the energy barrier to reversal under long current pulses to be ≃ 60 k B T 9 , 1/6 the macrospin value.…”
Section: A→bmentioning
confidence: 95%